Síntese citrato-hidrotermal e caracterização eletroquímica de LSCF para aplicação como catodo em célula a combustível de temperatura intermediária - Pereira, Laurênia Martins (2012)
The lanthanum strontium cobalt iron oxide (La1-xSrxCo1-yFeyO3 LSCF) is the most commonly used material for application as cathode in Solid Oxide Fuel Cells (SOFCs), mainly due to their high mixed ionic electronic conductivity between 600 and 800ºC. In this study, LSCF powders with different compositions were synthesized via a combination between citrate and hydrothermal methods. As-prepared powders were calcined from 700 to 900°C and then characterized by X-ray fluorescence, X-ray diffraction, thermal analyses, particle size analyses, nitrogen adsorption (BET) and scanning electronic microscopy. Films of composition La0,6Sr0,4Co0,2Fe0,8O3 (LSCF6428), powders calcined at 900°C, were screen-printed on gadolinium doped ceria (CGO) substrates and sintered between 1150 and 1200°C. The effects of level of sintering on the microstructure and electrochemical performance of electrodes were evaluated by scanning electronic microscopy and impedance spectroscopy. Area specific resistance (ASR) exhibited strong relation with the microstructure of the electrodes. The best electrochemical performance (0.18 ohm.cm2 at 800°C) was obtained for the cathode sintered at 1200°C for 2 h. The electrochemical activity can be further improved through surface activation by impregnation with PrOx, in this case the electrode area specific resistance decreases to values as low as 0.12 ohm.cm2 (800°C), 0.17 ohm.cm2 (750°C) and 0.31 ohm.cm2 (700°C). The results indicate that the citrate-hydrothermal method is suitable for the attainment of LSCF particulates with potential application as cathode component in intermediate temperature solid oxide fuel cells (IT-SOFCs)